The Effectiveness of Teaching Problem Solving Strategies According to Constructivism Theory on Mathematics Academic Achievement and Attitudes Toward Mathematics in Sixth Grade Elementary School Students - Zahra Kalati; Mohsen Rostamy-Malkhalife; Mohammad Hassan Behzadi (Iranian Journal of Educational Research, 2025)
Objective: The aim of the present study was to investigate the effectiveness of teaching problem solving strategies according to constructivism theory on mathematics academic achievement and attitudes toward mathematics in sixth grade elementary school students in Tehran. Methods: In a quasi-experimental study, 30 sixth grade students from elementary schools in Tehran were selected using convenience sampling and randomly assigned to experimental and control groups (15 students in each group). The teacher-made academic achievement test and the attitude scale toward mathematics lessons were used to collect data. In the experimental group, problem solving strategies based on the SOLO approach were implemented in seven stages, while the control group received conventional education. Results: The findings showed that teaching problem-solving strategies based on the SOLO approach can significantly increase academic achievement (T = 2.31, p < 0.05) and improve attitudes towards mathematics (T = 9.25, p < 0.05). Conclusions: Teaching according to Solo theory in mathematics significantly contributes to academic achievement and changes in students' attitudes toward mathematics. This method, by improving students' cognitive abilities and critical analysis, increases their self-confidence in dealing with complex problems and improves their attitudes toward this subject.